ExosomesNature’s Lipid Nanoparticles, a Rising Star in Drug Delivery and Diagnostics - Tenchov, Rumiana; Sasso, Janet M.; Wang, Xinmei; Liaw, Wen-Shing; Chen, Chun-An; Zhou, Qiongqiong Angela (ACS nano, 2022)
Exosomes are a subgroup of nanosized extracellular vesicles enclosed by a lipid bilayer membrane and secreted by most eukaryotic cells. They represent a route of intercellular communication and participate in a wide variety of physiological and pathological processes. The biological roles of exosomes rely on their bioactive cargos, including proteins, nucleic acids, and lipids, which are delivered to target cells. Their distinctive propertiesinnate stability, low immunogenicity, biocompatibility, and good biomembrane penetration capacityallow them to function as superior natural nanocarriers for efficient drug delivery. Another notably favorable clinical application of exosomes is in diagnostics. They hold various biomolecules from host cells, which are indicative of pathophysiological conditions; therefore, they are considered vital for biomarker discovery in clinical diagnostics. Here, we use data from the CAS Content Collection and provide a landscape overview of the current state and delineate trends in research advancement on exosome applications in therapeutics and diagnostics across time, geography, composition, cargo loading, and development pipelines. We discuss exosome composition and pathway, from their biogenesis and secretion from host cells to recipient cell uptake. We assess methods for exosome isolation and purification, their clinical applications in therapy and diagnostics, their development pipelines, the exploration goals of the companies, the assortment of diseases they aim to treat, development stages of their research, and publication trends. We hope this review will be useful for understanding the current knowledge in the field of medical applications of exosomes, in an effort to further solve the remaining challenges in fulfilling their potential.